2017
DOI: 10.1097/aud.0000000000000390
|View full text |Cite
|
Sign up to set email alerts
|

Optimizations for the Electrically-Evoked Stapedial Reflex Threshold Measurement in Cochlear Implant Recipients

Abstract: The results of this investigation demonstrate that the use of a standard 226 Hz probe tone is not ideal for measurement of the eSRT. The use of higher probe tone frequencies (i.e., 678 or 1000 Hz) resulted in lower eSRT levels when compared with the eSRT levels obtained with use of a 226 probe tone. In addition, 4 of the 23 participants included in this study did not have a measureable eSRT with use of a 226 Hz probe tone, but all of the participants had measureable eSRT with use of both the 678 and 1000 Hz pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 38 publications
1
24
0
2
Order By: Relevance
“…Emerging research has demonstrated that an ESRT response may be more successfully obtained at a lower stimulus level using a 1,000-Hz probe tone frequency or wideband reflectance compared with a conventional 226-Hz probe tone frequency. 48,49 However, the clinical implications (i.e., relationship of ESRT to C/M level) of these techniques are still unknown.…”
Section: Treatment and Follow-up Care For CI Usersmentioning
confidence: 99%
“…Emerging research has demonstrated that an ESRT response may be more successfully obtained at a lower stimulus level using a 1,000-Hz probe tone frequency or wideband reflectance compared with a conventional 226-Hz probe tone frequency. 48,49 However, the clinical implications (i.e., relationship of ESRT to C/M level) of these techniques are still unknown.…”
Section: Treatment and Follow-up Care For CI Usersmentioning
confidence: 99%
“…Cochlear implant (CI) is a surgically implanted system that electrically stimulates the auditory nerve in individuals with severe to profound hearing loss and who cannot benefit from conventional hearing aids (Wolfe et al, 2016). After surgery, each channel of the CI electrode stimulates the auditory nerve and each patient needs individualized programming of the CI system.…”
Section: Introductionmentioning
confidence: 99%
“…Although eCAP measures are the easiest objective electrical methods without any equipment other than CI fitting software, it is considered as a poor predictor of the behavioral thresholds (Wolfe et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations